Nox2-dependent neuroinflammation in an EAE model of multiple sclerosis - Ravelli Katherine G. (De Gruyter, 2019)
Multiple sclerosis (MS) is an inflammatory disease of the CNS, characterized by demyelination, focal inflammatory infiltrates and axonal damage. Oxidative stress has been linked to MS pathology. Previous studies have suggested the involvement of NADPH oxidase 2 (Nox2), an enzyme that catalyzes the reduction of oxygen to produce reactive oxygen species, in the MS pathogenesis. The mechanisms of Nox2 activation on MS are unknown. The purpose of this study was to investigate the effect of Nox2 deletion on experimental autoimmune encephalomyelitis (EAE) onset and severity, on astrocyte activation as well as on pro-inflammatory and anti-inflammatory cytokine induction in striatum and motor cortex.